The application of an assisting gas plasma generator for low-temperature magnetron sputtering of Ti-C-Mo-S antifriction coatings on titanium alloys; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Potekaev A. I.; Savostikov V. M.; Tabachenko A. N. Aleksandr Nikitich; Dudarev E. F.; Melnikova E. A.; Shulepov I. A. Ivan Anisimovich (2015, 2015)
Title screen